1986
DOI: 10.1017/s0031182000063496
|View full text |Cite
|
Sign up to set email alerts
|

Anin vivomodel for the study of chemotaxis induced by Schistosomula ofSchistosoma mansoni

Abstract: Peritoneal leucocytosis, with an increased percentage of eosinophils, was found in mice which had been infected with Schistosoma mansoni for 7 weeks or longer. Specific IgG against worm and egg antigens increased in peritoneal fluids and their corresponding sera respectively 5 and 7 weeks after infection. An intraperitoneal challenge with schistosomula elicited neutrophilia in all mice regardless of immune status, as well as infiltration of eosinophils and macrophages in infected mice. The secondary eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…As an advantage, peritoneal infection allows a simple and rapid method for mass screening of prophylactic agents to combat schistosomiasis (Pereira et al , 1974). This method of study has also helped to elucidate aspects of the early stages and immunology of the host–parasite relationship (Melo et al , 1978, 1980, 1993a, b, 1994; Melo & Pereira, 1980, 1985; Chao et al , 1986). Indeed, it has been demonstrated that parasites recovered from the peritoneal cavity of two albino mouse strains (AKR/J and Swiss) are significantly different in relation to the total body length of the worms, the intraperitoneal worm burden and the maturation degree of the schistosomes (Bicalho et al , 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As an advantage, peritoneal infection allows a simple and rapid method for mass screening of prophylactic agents to combat schistosomiasis (Pereira et al , 1974). This method of study has also helped to elucidate aspects of the early stages and immunology of the host–parasite relationship (Melo et al , 1978, 1980, 1993a, b, 1994; Melo & Pereira, 1980, 1985; Chao et al , 1986). Indeed, it has been demonstrated that parasites recovered from the peritoneal cavity of two albino mouse strains (AKR/J and Swiss) are significantly different in relation to the total body length of the worms, the intraperitoneal worm burden and the maturation degree of the schistosomes (Bicalho et al , 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have highlighted the macrophages or peritoneal cells as active role during S. mansoni infection by classical routes 3,11 or the neutrophils as an example of the first line defence in a peritoneal cavity of mice model 15,16 . However, little attention has been done to wholebody irradiation protocols in, which are might expect disable innate peritoneal resistance in mice against S. mansoni compared with other radiation protocols 13 .…”
Section: Introductionmentioning
confidence: 99%